End stage liver disease etiology & transplantation referral outcomes of major ethnic groups in British Columbia, Canada: A cohort study. Issue 42 (22nd October 2021) - Chahal, Daljeet; Marquez, Vladimir; Hussaini, Trana; Kim, Peter; Chung, Stephen W.; Segedi, Maja; Chartier-Plante, Stephanie; Scudamore, Charles H.; Erb, Siegfried R.; Salh, Baljinder; Yoshida, Eric M.
Abstract : Abstract: Liver disease etiology and transplantation outcomes may vary by ethnicity. We aimed to determine if disparities exist in our province. We reviewed the provincial database for liver transplant referrals. We stratified cohorts by ethnicity and analyzed disease etiology and outcomes. Four thousand nine hundred sixteen referrals included 220 South Asians, 413 Asians, 235 First Nations (Indigenous), and 2725 Caucasians. Predominant etiologies by ethnicity included alcohol (27.4%) and primary sclerosing cholangitis (PSC) (8.8%) in South Asians, hepatitis B (45.5%) and malignancy (13.9%) in Asians, primary biliary cholangitis (PBC) (33.2%) and autoimmune hepatitis (AIH) (10.8%) in First Nations, and hepatitis C (35.9%) in Caucasians. First Nations had lowest rate of transplantation (30.6%, P = .01) and highest rate of waitlist death (10.6%, P = .03). Median time from referral to transplantation (268 days) did not differ between ethnicities ( P = .47). Likelihood of transplantation increased with lower body mass index (BMI) (hazard ratio [HR] 0.99, P = .03), higher model for end stage liver disease (MELD) (HR 1.02, P < .01), or fulminant liver failure (HR 9.47, P < .01). Median time from referral to ineligibility status was 170 days, and shorter time was associated with increased MELD (HR 1.01, P < .01), increased age (HR 1.01, P < .01), fulminant liver failure (HR 2.56, P < .01) or South Asian ethnicity (HR 2.54, P < .01). Competing risks analysis revealed no differences in time to transplant ( P = .66) or time to ineligibility ( P = .91) but confirmed increased waitlist death for First Nations ( P = .04). We have noted emerging trends such as alcohol related liver disease and PSC in South Asians. First Nations have increased autoimmune liver disease, lower transplantation rates and higher waitlist deaths. These data have significance for designing ethnicity specific interventions. Abstract : Supplemental Digital Content is available in the text